Conservation of Transcription Start Sites within Genes across a Bacterial Genus - Wenjun Shao; Morgan N. Price; Adam M. Deutschbauer; Margaret F. Romine; Adam P. Arkin (mBio, 2014)
ABSTRACT Transcription start sites (TSSs) lying inside annotated genes, on the same or opposite strand, have been observed in diverse bacteria, but the function of these unexpected transcripts is unclear. Here, we use the metal-reducing bacterium Shewanella oneidensis MR-1 and its relatives to study the evolutionary conservation of unexpected TSSs. Using high-resolution tiling microarrays and 5′-end RNA sequencing, we identified 2,531 TSSs in S. oneidensis MR-1, of which 18% were located inside coding sequences (CDSs). Comparative transcriptome analysis with seven additional Shewanella species revealed that the majority (76%) of the TSSs within the upstream regions of annotated genes (gTSSs) were conserved. Thirty percent of the TSSs that were inside genes and on the sense strand (iTSSs) were also conserved. Sequence analysis around these iTSSs showed conserved promoter motifs, suggesting that many iTSS are under purifying selection. Furthermore, conserved iTSSs are enriched for regulatory motifs, suggesting that they are regulated, and they tend to eliminate polar effects, which confirms that they are functional. In contrast, the transcription of antisense TSSs located inside CDSs (aTSSs) was significantly less likely to be conserved (22%). However, aTSSs whose transcription was conserved often have conserved promoter motifs and drive the expression of nearby genes. Overall, our findings demonstrate that some internal TSSs are conserved and drive protein expression despite their unusual locations, but the majority are not conserved and may reflect noisy initiation of transcription rather than a biological function. IMPORTANCE The first step of gene expression is the initiation of transcription from promoters, which have been traditionally thought to be located upstream of genes. Recently, studies showed that in diverse bacteria, promoters are often located inside genes. It has not been clear if these unexpected promoters are important to the organism or if they result from transcriptional noise. Here, we identify and examine promoters in eight related bacterial species. Promoters that lie within genes on the sense strand are often conserved as locations and in their sequences. Furthermore, these promoters often affect the bacterium’s growth. Thus, many of these unexpected promoters are likely functional. Fewer promoters that lie within genes on the antisense strand are conserved, but the conserved ones seem to drive the expression of nearby genes.